Influence of soilless potting mix and root trainers on growth of rubber (Hevea brasiliensis Muell. Arg) seedlings - Adekunle, Salisu Monsuru (2017)
Rubber (Hevea brasiliensis) is an industrial crop that contributes significantly to the nation's economy. Nursery growers frequently report a decrease in the growth of rubber seedlings due to some negative impact of soils and other planting media. Adoption of new planting techniques like the use of soilless potting mix and root trainers (container) should be considered. Thus, the purpose of the study. In the first experiment, two newly produced soilless media, coded (M1and M2) one commercial soilless potting mix, M3 and M4 = soil-based medium as a control were evaluated with rubber seedlings. The plants grown on M1 whose composition included burnt rice husk (BRH), peat moss and urea-N (5%) increased plant stem diameter (5.5 mm/plant) and significantly different from the plants grown on M2 (3.82/plant), M3 (3.77 mm/plant) and M4 soil (3.12 mm/plant). The M1 equally gave the highest plant biomass yield. In the second experiment, the M2 whose composition included sugarcane bagasse, urea-N significantly improved scion stem diameter (6.26 mm/plant) compared to the plants grown on M1 (3.67 mm/plant), M3 (4.19 mm/plant) and M4 soil (4.42 mm/plant). Highest growth parameters like plant number of leaves, leaf area, leaf area index and plant biomass yield were significantly different p<0.05. There was relatively higher foliar nitrogen concentration in the plants that were grown on M2. In the third experiment, the planting media and water regimes (50%, 75%, 100% and 150% field capacity) were evaluated with rubber seedlings. The results indicated an interaction between the media and water regimes. Each of the media significantly influenced plant growth, biomass and water use efficiency (WUE). Noticeably, the growth of the plants corresponded to higher the WUEinstantaneous and WUEintrinsic whereby the M1 consistently increased plant growth such as leaf appearance rate (LAR) and biomass production and root morphological traits. Shoot dry weight of the plants was greater (14.66 g/plant) when 150% was applied and significantly different from M2 (10.36 g/plant), M3 (4.73 g/plant) and M4 6.22 g/plant. In the fourth experiment, immature rubber was evaluated with various sizes of root trainers 600 ml, 710 ml, 900 ml in volume and polybag size 15 × 20 cm designated as control. The root trainers, except for the polybag greatly increased plant growth. The biggest container 900 ml significantly maintained a higher leaf area index (10.18) compared to the plants that were grown in 600 ml (3.32), 710 ml (2.32) and polybag (6.17). Vegetative traits were significantly influenced whereby 900 ml gave the highest total fresh weight (22.86 g/plant) and significantly different from the plants grown in the 600 ml (13.68 g/plant), 710 ml (12.99 g/plant) and polybag (13.14 g/plant). The root trainer, 900 ml had resulted in the vigorous growth of the seedlings and it could be an ideal root trainer size for raising young-green budded of rubber. The newly produced soilless potting media especially the (M1) were superior in various capacities as remarkably shown in the rubber seedlings including the budded stump. Invariably, the new planting technique (soilless and root trainer), when compared to the traditional (soil and polybag-based) planting method is ideal for raising different types of planting stocks of rubber that would ensure a sustainable growth of the plant.